2011
DOI: 10.1007/s00259-011-1729-9
|View full text |Cite
|
Sign up to set email alerts
|

Duration of 18F-FDG avidity in lymph nodes after pandemic H1N1v and seasonal influenza vaccination

Abstract: Influenza vaccination may lead to FDG-avid draining lymph nodes beyond 1 month.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
64
4
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 8 publications
4
64
4
5
Order By: Relevance
“…The highest uptake typically occurred within the first 2 weeks after vaccination [1,3], but persisted beyond 1 month in some cases [2]. Additionally, lymph node size was normal [1][2][3][4], in contrast to our case. These reports advocate caution when considering changes to the treatment plan prior to confirmation of the suspected false-positive uptake.…”
contrasting
confidence: 69%
See 2 more Smart Citations
“…The highest uptake typically occurred within the first 2 weeks after vaccination [1,3], but persisted beyond 1 month in some cases [2]. Additionally, lymph node size was normal [1][2][3][4], in contrast to our case. These reports advocate caution when considering changes to the treatment plan prior to confirmation of the suspected false-positive uptake.…”
contrasting
confidence: 69%
“…Several previous reports demonstrated the occurrence of false-positive ipsilateral FDGavid axillary lymph nodes following vaccination [1][2][3][4]. The highest uptake typically occurred within the first 2 weeks after vaccination [1,3], but persisted beyond 1 month in some cases [2]. Additionally, lymph node size was normal [1][2][3][4], in contrast to our case.…”
contrasting
confidence: 67%
See 1 more Smart Citation
“…It has rather been described as an epiphenomenon in relation to the last vaccination campaigns against influenza A/H1N1 pandemic as seen in patients undergoing oncologic PET/CT [40][41][42] or in sporadic immunization cases [43,44]. Increased glucose metabolism in lymph nodes was not observable >14 days after immunization in the study by Burger et al [42] or >30-50 days by Thomassen et al [41], possibly due to the shorter stimulation time of these vaccines as opposed to the vaccine formulations used in the present study. Interestingly, Iyengar et al [45] found an association between PET-measured lymph node signals and viremia in HIV-infected patients that was attributed to CD4 lymphocyte activation in relation to HIV replication.…”
Section: Discussionmentioning
confidence: 99%
“…Ipsilateral lymph nodes metastases could not be ruled out due to the FDG uptake and the appearance on CT which showed marginally enlarged nodes with an eradicated fatty hilus. On the contrary the contralateral lymph nodes were less FDG-accumulating and had a preserved fatty hilus on CT, as observed in inflammatory lymph nodes (10). A drawback is, of course, that PET/CT may not be able to detect micrometastases (11).…”
Section: Discussionmentioning
confidence: 93%